2021
DOI: 10.1101/2021.03.07.434162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Event-Related Variability is Modulated by Task and Development

Abstract: Patterns of trial-averaged post-stimulus neural activity, e.g. event related potentials (ERPs) are traditionally interpreted as the correlates of cognitive operations. However, single-trial trajectories of neural responses approach these ERP components only in a loose and stochastic manner, questioning legitimacy of these components, proposed roles. Deconstructing the conventional ERP analyses, here we studied patterns of event related variability (ERV) in 2-6 month-old infants and adults using electroencepha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 96 publications
(172 reference statements)
0
16
0
Order By: Relevance
“…One possible explanation is that these methods are not optimal for infant data due to the intrinsic properties of the signal. For example, the high inter-trial variability observed in infants (Naik et al, 2021) might complicate the separation of variance related to evoked and non-evoked activity, as the method is based on the presence of highly reproducible activity across trials. The developmental changes and variability in infant EEG neural responses and physiological artifacts might also result in a poor decomposition during ICA for infant data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible explanation is that these methods are not optimal for infant data due to the intrinsic properties of the signal. For example, the high inter-trial variability observed in infants (Naik et al, 2021) might complicate the separation of variance related to evoked and non-evoked activity, as the method is based on the presence of highly reproducible activity across trials. The developmental changes and variability in infant EEG neural responses and physiological artifacts might also result in a poor decomposition during ICA for infant data.…”
Section: Discussionmentioning
confidence: 99%
“…The poor performances of the method are partially due to the nature of infant EEG data. Young infants' recordings contain more slow waves than adult data (Eisermann et al, 2013;Marshall et al, 2002), ERPs are less precise in time (Kushnerenko et al 2002) and more variable (Naik et al, 2021). The nature of the artifacts is also different in infants and adults.…”
Section: Independent Component Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the slow fluctuations (ERD/ERS) visible in trial-averaged power profiles cannot be detected in individual trials (e.g. Tallon-Baudry & Bertrand, 1996;Naik et al, 2021); they do emerge as new and abstract features from smoothing out inter-trial fluctuations, treated as uninformative noise. But, concretely, behavior is performed in each individual trial, and also varies from trial to trial.…”
Section: Introductionmentioning
confidence: 99%
“…Such coordination arises in a self-organized manner, as the system is constrained by global structural and dynamical determinants to sample lower-dimensional manifolds within the high-dimensional space of configurations it could theoretically access if its parts were separately controlled (Bressler & Kelso, 2001;Pillai & Jirsa, 2017). Structured behavior along a task would thus just be associated to transient adaptations of system's ongoing trajectories on these manifolds, rather than to abrupt reconfigurations (Shine et al, 2019;Naik et al, 2021). These dynamical system views are akin to early proposals that evoked activity and networks are very similar to spontaneous fluctuation patterns (Kenet et al, 2003;Cole et al, 2014, Naik et al, 2021, possibly reflecting capability for probabilistic computations (Orban et al, 2016).…”
Section: Introductionmentioning
confidence: 99%